Career Woman: The Dual Roles Conflict Management in the Gender Perspective - Yanti, Yulisma; Usman, Nasir; Bahrun, Bahrun (UIN Sunan Kudus, 2023)
Human rights are something that is essential and should not be limited only for reasons that refer to gender and social status, especially human rights for women in various aspects, especially the right to a career and self-actualization. Facts on the ground show that women also have the same competence as men in the aspects of public and professional roles. This study aims to analyze the aspects of women's rights and freedoms in carrying out their roles as career women, especially for women who are married and have dual roles. This study examines aspects of social roles and management of role conflicts that are experienced by women with the status of career women. Aspects of social roles are studied based on various theories of social development, studies of women's rights based on the concept of human rights and gender equality. The data in this study were sourced from the results of observations, interviews, and literature studies. The analysis technique used was an interactive model. The results of this study indicate that career women with dual roles have appropriate conflict management techniques, so that their roles have the same priority. This was also supported by the concept of gender equality which is starting to be accepted in society so that women can live a life with the dual roles they have, as well as the guarantee of human rights as human beings who have complete freedom.